Comment on “Tragic prototypes and their evolution in classical Chinese works” - Huo, Yifan (2024)
Commented Article: ZHANG, Yunpeng. Tragic prototypes and their evolution in classical Chinese works. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 4, “Eastern thought”, e0240084, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14688.